Proyecto de factibilidad para la creación de una empresa productora de camisetas de algodón para niños y su comercialización en la provincia del Azuay. - Ramos Tello, Eddie Omar (2012)
The current competitive conditions become necessary to analyze investment projects are planned a change in the design of products, processes, adaptation of machinery and equipment, personnel, ie required to redesign the administrative and organizational structure of the companies. The implementation of a production and marketing of cotton T-shirts for children allowed the application of different methods and techniques that enables research, as the inductive method that gave it a guideline to determine the overall conclusions of the project, the deductive method Based on this we determined the sample size, with general data and actual local population potential demand, real, effective and unmet demand, the analytical method that enabled synthetic, management science and applied whereby generalizing laws were established company producing cotton shirts for children, the statistical method however possible to measure the results of the survey also determined the highest percentage of which determined the issue of the feasibility of starting a business production and marketing of cotton T-shirts for children. In the market study in the province of Azuay, with a sample of 399 people and 281 traders (sports, stores, boutiques and shopping centers); tabulated surveys have been analyzed and the results have been inferred then perform analysis market, determining the potential demand of 2,564,610 t, 1,923,458 t real demand, 1.346.421camisetas effective demand, the supply of 255,420 t and 1,137,822 unmet demand, which allowed us to determine that the project can and should executed, the results obtained in the analysis of demand, supply and marketing levels for this product. The unmet demand reflects the market potential in the province aforesaid for this product, with the following results: For the first year of the project life is unmet demand: 1,137,822 cotton shirts, the installed capacity of the project determines that the company will be able to produce 657,000 t capacity of which will be used de156.600 cotton shirts for children, which will occur 70% of the capacity used for the first year which corresponds to 109,620 cotton shirts for children also determines the location of the same which will be located in the city of Cuenca, in the Industrial park streets, Av Octavio Chacon Vintimilla Moscoso and Cornelius. The production process involves the use of suitable equipment, which will be guaranteed to get a quality product and reasonable prices. Then develops the project engineering processes determining the diagrams, the operation and management features, technical requirements such as equipment, facilities, furniture and fixtures. Likewise, a study administrative determined as a Limited Liability Company, and functional organizational structure to the hierarchical levels both Legislative, Executive, Level Advisory Support Assistant level, operational level, as well as operating manuals, charts; which served as a guideline for implementing a good organization, since it will have the following staff: Manager, a Secretary, a Concierge-Guardian, an accountant who will be part of the administrative, and operational staff distributed as follows: a Head production, a sales manager, six workers and two sellers. The project reaches an investment of $ 93,340.64 and will be funded with a contribution of partners to 57% of total investment corresponding to $ 53,340.64 and a loan to keep the project to be the 43.00 Banco Pichincha % which corresponds to $ 40,000 5-year term at 15.20% interest per year. The financial evaluation shows the following results: According to the NPV of this project gives a positive value of $ 350,132.67, which indicates that the project or investment is suitable. For the current project IRR is 90.69%, this value being satisfactory for the project, the time it would take to recover the original investment would be 2 years, 1 month and 12 days, for this project, the sensitivity are less than one, therefore do not affect changes in project costs and increased revenue decreased 64% and 33%, respectively, ie the project is not sensitive to these changes. Among the most significant findings and recommendations have, that the market study developed in the province of Azuay, we determined that the project can and should be run by the results obtained in the analysis of supply and demand. It has been shown that there is a significant unmet demand of the product under development, which with the implementation of our business, at 100% capacity, will be covered by 23.83%. When this product to be known in the market as both have strong competition, it is necessary to implement an ongoing campaign using existing facilities as it says in our marketing proposal.